A Wideband Full-Corporate-Feed Waveguide Slot Planar Array - Zhou Shi-Gang; Huang Guan-Long; Peng Zhao-hang; Li-Jian Ying (IEEE transactions on antennas and propagation, 2016)
A wideband full-metal planar antenna array with full-corporate feed-network is proposed. Cavity and slot are used as the basic radiation element and T-shaped walls are employed in the cavity to achieve wide bandwidth. E-plane waveguide feed-network configuration is utilized so as to suppress wave leakage between adjacent layers when the antenna is fabricated by a conventional machining technique. An 8 × 8 antenna array prototype with optimized parameters is tested. Experimental results show that the bandwidth of VSWR <; 2.0 is up to 36.9% (10.24 - 14.87 GHz). More than 60% aperture efficiency and higher than 23.4 dBi gain are achieved over the operational bandwidth.